The effect of pH and type of silicone on cotton and polyester finished fabrics - Atikah, Wulan Safrihatini; Salis, Witri Aini; Permana, Lingga; Redya, Brilyan Muhammad (Jurnal Pendidikan Kimia, 2024)
A Characteristic often found in textile products is softness. The compound widely used as softener is silicone compound. The aim of this research is to determine the properties that will be obtained from the type of fabric being processed by comparing the use of silicon types, namely amino-propyl-functional polydimethyl siloxane (PDMS) and blocked amino silicone to each fabric. Firstly, research was conducted by varying the pH of the finishing process. Determined optimum pH will be followed by determining concentration of 15“60 g/L for each type silicone. The experiments was carried out on pad- dry- cure method. The tests carried out include fabric stiffness, tensile strength, resistance to repeated washing and heat, yellowing effect, Fabric Touch Tester and Water Contact Angle testing. It was found that there was no significant influence of pH on the use of amino-propyl-functional polydimethyl siloxane and blocked amino silicone compounds, so the next process was carried out at pH 7. Increasing the concentration of the softener will provide a better softening effect and optimum concentration at 45 g/L for both types of fabric used. Blocked amino silicone has better resistance to repeated washing compared to amino-propyl-functional polydimethyl siloxane. Heat testing shows that differences in molecular structure have no influence on both fabrics. Fabric processed using amino-propyl-functional polydimethyl siloxane provides a yellowing effect. Amino-propyl-functional polydimethyl siloxane provides good hydrophilicity. The softness value of blocked amino silicone is better performance on cotton fabric.